PENGARUH GREEN PACKAGING, GREEN ADVERTISING, GREEN PERCEIVED VALUE, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN THE BODY SHOP - Ewa Damayanti; Audita Nuvriasari (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This study aims to analyze the influence of green packaging, green advertising, green perceived value, and brand image on consumer purchasing decisions of The Body Shop, and to see which variables most influence The Body Shop's consumer purchasing decisions. This research was conducted with a quantitative approach. Primary data collection was conducted by disseminating questionnaires to a sample of 70 respondents who were at least 17 years old, purchasing products at one of The Body Shop outlets, namely at Malioboro Mall, Ambarrukmo Plaza, Hartono Mall, Galeria Mall, or Jogja City Mall, Special Region of Yogyakarta, and purchasing The Body Shop products between January 2020 and March 2021. The data analysis used in this study was a multiple linear regression test. The results of this study showed that partially green packaging, green advertising and brand image had no positive and significant effect on purchasing decisions. While green perceived value positively and significantly influenced the purchase decision. Green perceived value is the most dominant variable that had positive and significant effect on purchasing decisions. The Body Shop should improve the green packaging strategy that is being implemented, expand the reach of green advertising, increase the green perceived value of consumers, and increase the brand image of The Body Shop.